Blood Lead Levels in Opium-Poisoned Children: One Cross-Sectional Study in Iran - Chouhdari, Arezoo (Addict Health, 2020)
BACKGROUND: Lead poisoning is now more common due to accidental or intentional exposure to opium impregnated with lead. We aimed to determine the relationship between the blood lead levels (BLLs) and basic characteristics in opium-poisoned children. METHODS: In this cross-sectional study, 32 children younger than 13 years old who had been admitted to Loghman Hakim Poison Center, Tehran, Iran, due to opium poisoning, were evaluated for BLLs. Patients’ demographics, symptoms, signs, and lab tests were evaluated as well as the BLLs. FINDINGS: The median and range of age in children with opium poisoning were 14 and 141 months with minimum and maximum age of 3 and 144 months, respectively, and 62.5% were boys. Their mean BLL was 9.78 ± 3.44 μg/dl and in 70% of opium-poisoned children, BLL was ≥ 5 μg/dl. There was a significant difference between mean BLLs in girls and boys (17.07 ± 6.57 μg/dl in girls and 6.61 ± 3.22 μg/dl in boys, P = 0.02). We found a significant correlation between BLL and hemoglobin (Hb) level. In very low Hb level (< 8 g/dl), the BLL was higher but with increasing Hb level, BLL increased as well; in Hb levels > 14 g/dl, BLL decreased again (P = 0.01). CONCLUSION: Although none of the children needed chelation therapy, strategies should be developed to prevent children from being exposed to opium and other materials impregnated with lead regarding its effects on all organs of children.